2021
DOI: 10.3390/en14030619
|View full text |Cite
|
Sign up to set email alerts
|

Improved Metaheuristic Optimization Algorithm Applied to Hydrogen Fuel Cell and Photovoltaic Cell Parameter Extraction

Abstract: As carriers of green energy, proton exchange membrane fuel cells (PEMFCs) and photovoltaic (PV) cells are complex and nonlinear multivariate systems. For simulation analysis, optimization control, efficacy prediction, and fault diagnosis, it is crucial to rapidly and accurately establish reliability modules and extract parameters from the system modules. This study employed three types of particle swarm optimization (PSO) algorithms to find the optimal parameters of two energy models by minimizing the sum squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Some of other metaheuristic algorithms utilized in the literature are artificial bee swarm optimization (ABSO) [21], biogeography-based optimization with mutation strategies (BBO-M) [22], bacterial foraging algorithm (BFA) [23], bird mating optimizer (BMO) [24], grouping-based global harmony search (GGHS) [25], generalized oppositional teaching-learning-based optimization (GOTLBO) [26], improved whale optimization algorithm (IWOA) [27], pattern search (PS) [28], simulated annealing (SA) [29], self-adaptive teaching-learning-based optimization (SATLBO) [30], hybrid methods [31][32][33][34][35], etc. These metaheuristic approaches also suffer from different inherent characteristics, such as premature convergence, weak exploitation, high sensitivity to the initial population and adherence to the limited number of parameters for performance improvement [36][37][38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of other metaheuristic algorithms utilized in the literature are artificial bee swarm optimization (ABSO) [21], biogeography-based optimization with mutation strategies (BBO-M) [22], bacterial foraging algorithm (BFA) [23], bird mating optimizer (BMO) [24], grouping-based global harmony search (GGHS) [25], generalized oppositional teaching-learning-based optimization (GOTLBO) [26], improved whale optimization algorithm (IWOA) [27], pattern search (PS) [28], simulated annealing (SA) [29], self-adaptive teaching-learning-based optimization (SATLBO) [30], hybrid methods [31][32][33][34][35], etc. These metaheuristic approaches also suffer from different inherent characteristics, such as premature convergence, weak exploitation, high sensitivity to the initial population and adherence to the limited number of parameters for performance improvement [36][37][38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The recent literature [14][15][16][17][18][19][20] has shown that using metaheuristic-based techniques can be so useful for solving such complex nonlinear problems. Indeed, metaheuristics are computational intelligence paradigms used especially for the sophisticated solving of optimization problems.…”
Section: Introductionmentioning
confidence: 99%
“…With minimal problem-specific knowledge required, metaheuristics are easy to implement and can be tailored to various domains. Different metaheuristics were used in the field of renewable energy such as PSO [14], artificial bee colony (ABC) [15], whale optimization algorithms (WOA) [16], genetic algorithm (GA) [17] and ant colony optimization (ACO) [18]. Azar et al [19] used the Battle Royale Optimization Algorithm (DBRA) to effectively identify the undetermined parameters in solid oxide fuel cell models.…”
Section: Introductionmentioning
confidence: 99%